The Role of Parental Education in Prevention of Malnutrition in Early Childhood - Adawiyah, Fatimah; Achdiani, Yani (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2025)
Malnutrition is a condition where a person lacks nutritional intake in the body, this will certainly hamper the development of children and this is where the role of parents is important to prevent malnutrition. The research method used is a literature study with the acquisition of research data for a maximum of 10 years back. The results obtained are that the role of parental education such as attitude education, food parenting education, knowledge education through information education and nutrition knowledge education in parents plays an important role in preventing malnutrition. The conclusion is that the role of parental education is very important so that children can fulfill their nutrition optimally.